Transforming Indonesia's Food Security: Navigating Fertilizer Supply Challenges Amidst the Russia-Ukraine Conflict - Harinda, Amalia Izah; Al-Fadhat, Muhammad Faris (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to analyze the impact of the Russia-Ukraine conflict on Indonesia's food security, focusing on fertilizer supply disruptions and strategies for diversifying import sources. The urgency of this issue is underscored by Indonesia's heavy reliance on imported fertilizers, which are crucial for maintaining agricultural productivity. The research question centers on how Indonesia can mitigate the effects of regional conflicts on its food security and whether it should seek new partners for fertilizer imports. Utilizing a qualitative descriptive method, the study analyzes secondary sources, including books, scientific journals, and reliable online sources, from 2019 to 2024. The results indicate that the conflict has significantly disrupted Indonesia's fertilizer supply chain, leading to shortages and price hikes that affect agricultural productivity. The study highlights the importance of diversifying import sources, optimizing domestic production, and adopting modern agricultural technologies. Additionally, the research connects Malthusian theory with contemporary food security challenges, emphasizing the need for sustainable food production to keep pace with population growth. These findings contribute to the understanding of food security issues in Indonesia and provide insights for developing more resilient food security policies in the face of global conflicts.